Evaluating the environmental sustainability of energy crops: A life cycle assessment of Spanish rapeseed and Argentinean soybean cultivation - Fernández-Tirado, Francisca; Parra-López, Carlos; Romero-Gámez, Mercedes (Spanish Journal of Agricultural Research, 2017)
Rapeseed oil is expected to be increasingly used in Spain as raw material to produce biodiesel to the detriment of extra-EU imports of biodiesel mainly based on soybean oil from Argentina. Therefore, the environmental impacts produced throughout the life cycle of energy crops used to produce biodiesel which is consumed in Spain could be radically affected. In this context, the environmental impacts of rapeseed cultivation in Spain and soybean cultivation in Argentina, were compared under certain growing conditions using Life Cycle Assessment (LCA). Two methods of calculation for Life Cycle Impact Assessment (LCIA) and two functional units (FUs) were used to test potential biases. The results showed that the cultivation of soybean in Argentina had, in general, fewer environmental impacts than rapeseed cultivation in Spain when the FU was the area of cultivation, but these findings are inverted when the analysis is conducted according to the energy content of the biodiesel obtained from these crops. Soybean in fact has very low oil content, meaning that larger areas of land are required to obtain the same amount of biodiesel and that consequently it has a higher environmental impact by energy content. Fertilization was, in general, the process that generated the greatest environmental burdens, and is an area in which improvement is necessary in order to increase sustainability, particularly with regard to Spanish rapeseed.